KEEFEKTIFAN METODE OUTDOOR STUDY TERHADAP MINAT DAN HASIL BELAJAR PADA MUATAN MATEMATIKA DI SDN KRASAK 01 - Wulan Novita Sari; Rila Melyana Fitri; Yasin (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
This research aims to determine the effectiveness of the outdoor study method on interest and learning outcomes in mathematics content at SD N Krasak 01 and SD N Karangsembung 4. This research uses quantitative data collection techniques with questions. This research consists of 3 variables, First, Outdoor Study (X1) and learning outcomes (Y2), Interest in learning (Y1). This data collection uses a random sampling technique. So data was obtained, namely the effectiveness of the outdoor study method on interest and learning outcomes in mathematics content in elementary school. The results of this research prove that the first hypothesis is accepted, which means that the effectiveness of the outdoor study method on interest and learning outcomes in elementary schools has a positive and significant influence on interest and learning outcomes in SD N Krasak 01 and SDN Karangsembung 04. So it can be concluded that research regarding the effectiveness of the outdoor method study of interest and learning outcomes for mathematics content in elementary school. Based on the average learning outcomes obtained in elementary school mathematics content, it shows that the average learning outcome for the experimental class is 63.40 higher than the control class which has an average of 59.50 on average. The average of this score is then tested for a hypothesis or t test on variable Y1 or the study result variable is consulted with the specified value, namely 0.05. The basis for the decision is that if the value is sig 0.05 or Tcount>Ttable, then there is an influence of variable x on variable y. Based on the average obtained by the experimental class and the control class, the experimental class received a higher average value compared to the average value of the control class. The experimental class got an average score of 63.40 and the control class got a score of 49.00. From the results of the t